OVERVIEW AND UPDATE OF BIRD RECORDS FROM THE TROPICAL ANDES: IMBABURA PROVINCE, ECUADOR - Caula Quintero, Sabina Amparo (El Hornero, 2025)
Historically, bird lists have constituted a powerful instrument for developing effective legal conservation measures. I present a list of birds from Imbabura Province, which is part of the Tropical Andes, the world’s most biologically diverse area. Although Imbabura has been established as a UNESCO Global Geopark and 35% of its surface is protected, the province also has an extensive history of landscape fragmentation and habitat degradation that dates back to pre-Columbian times. I looked through and selected records from the GBIF database (1818–2022). This database considers any biodiversity information sources, from museum specimens, the records of eBird birdwatchers to georeferences of smartphone photos shared by naturalists. I also examined the Google Scholar database and thesis digital repositories, searching for references with records of Imbabura birds. I extracted the geographic coordinates of more recent bird sighting sites (2018-2020), and I uploaded them into a geographic information system overlaid with a land use cover layer. I used 4 classes for land use: (1) URB, anthropic zone; (2) AGR, agricultural land; (3) NAT, both forest as shrubby and herbaceous vegetation; and (4) AQU, water bodies. I estimated each species’ occurrence in each landscape. The results are an inventory of 753 bird species recorded in Imbabura, with 146 species categorized under some threat level. Due to the high number of bird species observed at Imbabura, 45% of Ecuador birds, public policies, and civil awareness are necessary to engage in conservation actions and other activities supporting the maintenance of this biodiversity. This study underscores the importance of citizen science and free database platforms for research.
Actualización de los registros de aves en la provincia de Imbabura, ubicada en los Andes tropicales de Ecuador
Las listas de aves han sido instrumentos poderosos para desarrollar medidas efectivas de conservación. En este trabajo se presenta una lista de aves de la provincia de Imbabura, que forma parte de los Andes Tropicales, la zona con la mayor diversidad biológica del mundo. A pesar de que Imbabura ha sido reconocida como Geoparque Mundial de la UNESCO y el 35% de su superficie está protegida, la localidad también cuenta con una extensa historia de fragmentación del paisaje y degradación del hábitat que se remonta a la época precolombina. Se seleccionaron los registros de aves para Imbabura, en GBIF (1818-2022). También se examinó Google Scholar y los repositorios digitales de tesis, buscando referencias con registros de aves de la provincia. Los sitios de avistamiento de aves más recientes (2018-2020), se cargaron en un sistema de información geográfica y se vincularon a una capa de cobertura de uso del suelo. Se usaron 4 categorías: (1) URB, zona antrópica; (2) AGR, tierra agrícola; (3) NAT, tanto bosque como vegetación arbustiva y herbácea; y (4) AQU, cuerpos de agua. Se calculó la ocurrencia de cada especie en cada tipo de paisaje. Los resultados son un inventario de 753 especies registradas en Imbabura, con 146 en alguna categoría de amenaza. Debido a la gran cantidad de aves en esta provincia, las cuales representan el 45% de las especies registradas en Ecuador, es fundamental implementar políticas públicas en apoyo a la conservación de esta biodiversidad. Este estudio resalta la relevancia de la ciencia ciudadana y las plataformas de bases de datos gratuitas como herramientas de apoyo a la investigación.
Keywords: Andes tropicales; aves; avifauna; conservación; geoparque mundial; hotspot; minería